THE INFLUENCE OF THE QUALITY OF GENERAL HEALTH CENTER UNIT ON PATIENT SATISFACTION IN THE PRIMARY HEALTH CENTERS OF SOUTH LAMPUNG REGENCY, LAMPUNG PROVINCE - Susi, Susilawati; Lubis, Samran; Lubis, Basyariah (JURNAL KESMAS DAN GIZI (JKG), 2023)
The mismatch in the healthcare workforce ratio leads to suboptimal healthcare services in community health centers (Puskesmas). The quality of healthcare services needs to be evaluated from the perspective of both the institution and the patients, as interpreted through the community satisfaction index. This study utilized cluster randomized sampling. Data collection techniques included observation and questionnaires. The population of this study consisted of the number of outpatient visits in 7 (seven) medium-sized community health centers in South Lampung Regency in 2020, totaling 287,279 visits. The sample size for this study was 347 samples in each group. The study was conducted from February to March 2023. The aim of this research is to analyze the influence of healthcare service quality on patient satisfaction index in Community Health Centers in South Lampung Regency, focusing on the dimensions of Reliability, Assurance, Tangibles, Empathy, and Responsiveness (SERVQUAL). The results of this study showed that the Community Satisfaction Index (CSI) for healthcare services had a mean quality scale of 3.09, indicating a "Good" index. Regarding healthcare service quality, in terms of the SERVQUAL measurement variables, there is still 1.2% of the population stating that the quality of services in community health centers is not good, specifically in the aspect of Empathy. The significance value (P=0.00) indicates that service quality significantly affects the CSI, with a coefficient of determination (R square) of 0.685. Recommendations from this study suggest that the government of South Lampung Regency should provide special training for healthcare workers in community health centers to improve their skills in terms of their behavior and empathy towards patients, as well as to improve the ratio between healthcare personnel and the number of patient visits.